POSTURAL EVALUATION: CHANGES IN THE SPINE OF HIGH SCHOOL STUDENTS (Fiep Bulletin - online, 2011)
INTRODUCTION According Magee (2002), posture is one composed of positions of the different joints of the human body in that moment, with the correct posture to a position where a minimum of stress is applied to each joint. When we conduct a study on the posture of adolescents who attend high school, we must consider the influence that the environment exerts on the activities and habits developed and adopted by individuals. The classrooms of the schools evaluated following the same patterns of organization from the beginning of the twentieth century, chairs are lined, forming three or four rows in the room, the table of teacher ahead, around the table. The posture of the spine is influenced by the routine in the classroom. The biomechanical model of the spine of man was not made to stay for long periods in the sitting position, maintaining fixed postures and repetitive movements (SEYMOUR, 1995). Whereas a teenager remains more than four hours a day in school, sitting in chairs that are ergonomically designed to meet specific needs of each student, but in general can serve all, it is important to perform a postural assessment in this population. OBJECTIVES To evaluate the attitude of high school students, identify and describe the main changes in the alignment of the vertebral column.METHODOLOGY This is a study of diagnostic, descriptive and exploratory. The selected population for the study was students who were regularly enrolled in school, in four schools, two public and two private city of Palmas - TO. The sample of this study was composed of 300 pupils, between thirteen and seventeen. Being 150 male and 150 female study participants were randomly selected. The protocol for data collection was based on studies of Kendall et al .(1987) e Kanoplich (2003). The student was placed in the standing position in simetógrafo with heels slightly apart and feet abducted about 15 degrees, seeking to asymmetries in the frontal, sagittal and transversal. In the observation anteroposterior body symmetries were identified at the hip, triangle tales, shoulders and head, side or in the profile we look at the hip. In the analysis postero-anterior were observed gluteal line, column ( lumbar, thoracic and neck), shoulder and head position. DISCUSSION The data indicate that there is an incidence of postural changes in the spine of the sample investigated. 4.7% in the cervical curvature (hyperlordosis), 11% in the thoracic curvature (hyperkyphosis), 18% lumbar curvature (hyperlordosis), 21% likely thoracic scoliosis, 4% likely lumbar scoliosis. CONSIDERATIONS Given the results obtained by evaluation of posture, it appears that there are changes of curvatures and lateral deviation of the vertebral column.